Wind-Driven Upwelling Dynamics in the Southwest Arafura Sea - Nabila Nur Hanifah; I Wayan Nurjaya; Yuli Naulita; Nyoman M. N. Natih (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2026)
This study examines the spatial and temporal variability of upwelling in the southwestern Arafura Sea, focusing on the influence of monsoonal winds and ENSO variability. The objective is to identify the physical mechanisms driving upwelling formation in the region. Satellite-derived sea surface temperature (SST) and chlorophyll-a data from 2010, 2015, and 2020 were analyzed during the Southeast Monsoon (June–August). In addition, wind data, surface currents, Ekman Mass Transport (EMT), and Ekman Pumping Velocity (EPV) were evaluated to investigate the underlying oceanographic processes. The results indicate that intensified southeasterly winds during the Southeast Monsoon enhance offshore Ekman transport and generate negative wind stress curl, leading to significant Ekman pumping with EPV values reaching up to −2.1 × 10⁻⁵ m/s. These processes promote the upwelling of cooler, nutrient-rich subsurface waters, as reflected by decreased SST and increased chlorophyll-a concentrations. Conversely, weaker wind forcing reduces Ekman dynamics and weakens upwelling intensity. Vertical profiles further confirm thermocline shoaling and the upward displacement of subsurface waters during strong wind conditions. In conclusion, upwelling variability in the southwestern Arafura Sea is primarily controlled by seasonal monsoonal winds and large-scale climate variability, while regional circulation, such as the Indonesian Throughflow, contributes to the availability of cooler subsurface water that enhances surface cooling when uplifted by Ekman processes.